2020
DOI: 10.1002/ece3.6753
|View full text |Cite
|
Sign up to set email alerts
|

Toward reliable habitat suitability and accessibility models in an era of multiple environmental stressors

Abstract: Global biodiversity declines, largely driven by climate and land‐use changes, urge the development of transparent guidelines for effective conservation strategies. Species distribution modeling (SDM) is a widely used approach for predicting potential shifts in species distributions, which can in turn support ecological conservation where environmental change is expected to impact population and community dynamics. Improvements in SDM accuracy through incorporating intra‐ and interspecific processes have booste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 198 publications
(326 reference statements)
1
21
1
Order By: Relevance
“…This presents a clear challenge to developing proactive management systems; as well as the need to understand and monitor the formation of novel invasive weed ecotypes, there is the need to manage ecosystems for greater resistance to invasion. Climate modeling approaches for invasive plants to this point have largely relied on large-scale geographic inputs (e.g., regional, national or international scales), but ecosystem resistance tends to act at local levels, and thus there is a need to research the potential for finer-scale modeling (Bradley, 2016;De Kort et al, 2020). Weed researchers conducting a horizon scan of weed research priorities identified the underlying challenges largely related to combining agroecological, socio-economic and technological approaches (Neve et al, 2018).…”
Section: Future Research Needsmentioning
confidence: 99%
“…This presents a clear challenge to developing proactive management systems; as well as the need to understand and monitor the formation of novel invasive weed ecotypes, there is the need to manage ecosystems for greater resistance to invasion. Climate modeling approaches for invasive plants to this point have largely relied on large-scale geographic inputs (e.g., regional, national or international scales), but ecosystem resistance tends to act at local levels, and thus there is a need to research the potential for finer-scale modeling (Bradley, 2016;De Kort et al, 2020). Weed researchers conducting a horizon scan of weed research priorities identified the underlying challenges largely related to combining agroecological, socio-economic and technological approaches (Neve et al, 2018).…”
Section: Future Research Needsmentioning
confidence: 99%
“…Additionally, processes shaping extant molecular diversity of temperate marine species have predominantly been investigated in the Northern Hemisphere, where glaciation events and variation in ice sheets differ profoundly from Southern Hemisphere coastal systems (Velichko et al, 1997), many of which did not have ice cover at the height of the most recent glaciation. Lastly, drivers of molecular diversity are also usually investigated either visually with habitat suitability maps (Assis et al, 2014; Chefaoui et al, 2017; Neiva et al, 2014) or statistically with linear models (Acevedo‐Limón et al, 2020; De Kort et al, 2020; Manel et al, 2020), but rarely with both approaches. The prevailing processes driving intraspecific diversity can be inferred with more certainty when both visual and statistical analyses are combined (Yannic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Different drivers of molecular diversity can be expected in marine than terrestrial species, as global trends of intraspecific diversity differ between the two, with marine taxa showing strong latitudinal trends (Manel et al, 2020), whereas terrestrial taxa do not (De Kort et al, 2020). Many inferences of molecular diversity are also often obtained from a single marker, which has its owns caveats, as markers like mitochondrial DNA (mtDNA) are expected to reflect more historical processes compared with other markers such as genome-wide single-nucleotide polymorphisms (SNPs; Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our modelling approach combined multi-temporal occurrence records with year-specific land use/cover data to assess range change and potential drivers of distribution. There is a growing realization of the important role that land cover data plays within species distribution modelling (Chauvier et al, 2021;Kort et al, 2020), especially at different temporal and spatial scales as a proxy for key processes of ecosystem functioning controlling species distribution and abundance patterns (Arenas-Castro et al, 2019). However, incorporating time series of land cover data has followed different approaches, for example, by calculating seasonal variation in land cover (or vegetation indices) at occurrence points (e.g.…”
Section: Discussionmentioning
confidence: 99%